Differential Expression of Genes for Cyclin-Dependent Protein Kinases in Rice Plants - Umeda, Masaaki (American Society of Plant Physiologists, 1999)
Cyclin-dependent protein kinases (CDKs) play key roles in regulating the eukaryotic cell cycle. We have analyzed the expression of four rice (Oryza sativa) CDK genes, cdc2Os1, cdc2Os2, cdc2Os3, and R2, by in situ hybridization of sections of root apices. Transcripts of cdc2Os1, cdc2Os2, and R2 were detected uniformly in the dividing region of the root apex. cdc2Os1 and cdc2Os2 were also expressed in differentiated cells such as those in the sclerenchyma, pericycle, and parenchyma of the central cylinder. By contrast, signals corresponding to transcripts of cdc2Os3 were distributed only in patches in the dividing region. Counterstaining of sections with 4′,6-diamidino-2-phenylindole and double-target in situ hybridization with a probe for histone H4 transcripts revealed that cdc2Os3 transcripts were abundant from the G(2) to the M phase, but were less abundant or absent during the S phase. The levels of the Cdc2Os3 protein and its associated histone H1-kinase activity were reduced by treatment of cultured cells with hydroxyurea, which blocks cycling cells at the onset of the S phase. Our results suggest that domains other than the conserved amino acid sequence (the PSTAIRE motif) have important roles in the function of non-PSTAIRE CDKs in distinct cell-cycle phases.